Twelve ways to confirm targets of activity-based probes in plants - Kovács, J; van der Hoorn, R (Elsevier, 2016)
Activity-based probes are powerful tools to interrogate the functional proteome. Their covalent and often irreversible labeling of proteins facilitates the purification, identification and quantification of labeled proteins. However, the detection of labeled proteins often requires a confirmation, especially when unexpected proteins are identified, or to unravel fluorescent activity profiles. Here, we review twelve approaches towards target confirmation, grouped in approaches by direct target detection, target expression or target depletion. We discuss their proper use and limitations and illustrate these approaches with examples from plant science.